Detection of sister-species in invasive populations of the fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) from Uganda - Otim, Michael H.; Tay, Wee T.; Walsh, Thomas K.; Kanyesigye, Dalton; Adumo, Stella; Abongosi, Joseph; Ochen, Stephen; Sserumaga, Julius; Alibu, Simon; Abalo, Grace (PloS one, 2018)
The fall armyworm (FAW) Spodoptera frugiperda (J. E. Smith) is a species native to the Americas. This polyphagous lepidopteran pest was first reported in Nigeria and the Democratic Republic of São TomeÂ and Principe in 2016, but its presence in eastern Africa has not been confirmed via molecular characterisation. In this study, FAW specimens from western and central Uganda were identified based on the partial mtDNA COI gene sequences, with mtDNA COI haplotypes matching those identified in Nigeria and São TomeÂ . In this study, we sequence an additional partial mtDNA Cyt b gene and also the partial mtDNA COIII gene in Ugandan FAW samples. We detected identical mitochondrial DNA haplotypes for both the mtDNA Cyt b and COI partial genes, while combining the mtDNA COI/Cyt b haplotypes and mtDNA COIII haplotypes enabled a new maternal lineage in the Ugandan corn-preferred FAW samples to be identified. Our results suggested that the African incursions of S. frugiperda involved at least three maternal lineages. Recent full genome, phylogenetic and microsatellite analyses provided evidence to support S. frugiperda as likely consisted of two sympatric sister species known as the corn-preferred and rice-preferred strains. In our Ugandan FAW populations, we identified the presence of mtDNA haplotypes representative of both sister species.
Keywords: Detection; sister-species; populations; Lepidoptera